A systematic review of gallstone sigmoid ileus management. (March 2018) - Farkas, Nicholas; Kaur, Vasha; Shanmuganandan, Arun; Black, John; Redon, Chantal; Frampton, Adam E.; West, Nicholas
Abstract: Introduction: Gallstone sigmoid ileus is a rare although serious complication of cholelithiasis resulting in large bowel obstruction. The condition accounts for 4% of all gallstone ileus patients. There are no recognized management guidelines currently. Management strategies range from minimally invasive endoscopy and lithotripsy to substantial surgery. We aim to identify trends when managing patients with gallstone sigmoid ileus to help improve outcomes. Methods: Literature searches of EMBASE, Medline and by hand were conducted. All English language papers published from 2000 to 2017(Oct) were included. The terms 'gallstone', 'sigmoid', 'colon', 'ileus', 'coleus' and 'large bowel obstruction' were used. Results: 38 papers included, male:female ratio was 8:30. Average age was 81.11 (SD ± 7.59). Average length of preceding symptoms was 5.31days (+/-SD3.16). 20/38 (59%) had diverticulosis. 89% of patients had significant comorbidities documented. 34/38 patients underwent computerized tomography. 31 stones were located within sigmoid colon, 4 at rectosigmoid junction and 2 within descending colon. Average impacted gallstone size was 4.14 cm (2.3–7 cm range). 23/38 (61%) patients' initial management was conservative or with endoscopy ± lithotripsy. Conservative management successfully treated 26% of patients. 28/38 (74%) patients ultimately underwent surgical intervention. 5/38 patients died post-operatively. Patients treated non-operatively had shorter hospital stays (4:12.3days) although not significant (p-value = 0.0056). Conclusions: There is no management consensus from the literature. Current evidence highlights endoscopy and lithotripsy as practical firstline strategies. However, surgical intervention should not be delayed if non-operative measures fail or in emergency. Given the complexity of such patients, less invasive timesaving surgery appears practical, avoiding bowel resection and associated complications. Highlights: Comprehensive review of treatment modalities when managing gallstone sigmoid ileus. Endoscopy and lithotripsy appear practical first-line strategies in stable patients. Minimally invasive surgery confers less risk in this cohort. Surgery should not be delayed in the emergency setting.